Aromatic profiling of Zanthoxylum myriacanthum (makwhaen) essential oils from dried fruits using different initial drying techniques - Trid Sriwichai (2019)
© 2019 Elsevier B.V. Initial drying techniques have direct impacts on the aromatic characteristics of Makwhaen (Zanthoxylum myriacanthum) fruit essential oil, the new source of natural scent for the fragrance industries. This research aims at investigating the aromatic profiles of hydro-distillated oils from the dried fruits that underwent following conventional drying techniques: sun drying, full-shade drying; and artificial heat drying techniques: oven drying (60 °C), microwave drying at 300 and 450 W (Mic300 and Mic450). The chemical profile of each essential oil was analysed by Gas Chromatography-Mass Spectrometry (GC–MS) and their sensorial attributes were assessed by descriptive analysis. Microwave drying was suitable to dry the fruits based on Fick's model. The essential oils mainly contained chemical compounds representing citrus, woody and fruity characteristics (i.e., limonene, sabinene, α-pinene and β-phellandrene). Dried fruits of different drying techniques gave variations in the chemical profiles. Calculated Odour Activity Value (OAV) advised that the citrus scent was the most powerful when the raw material was dried using microwave at 450 W. The Principle Component Analysis (PCA) of the volatile compounds grouped shade drying and Mic300 into the same cluster. Terms pine, citrus, herb, spice, sweet and woody were selected for descriptive analysis. Essential oil from the fresh fruits illustrates low intensities of those attribute as compared with that of dried samples. The preference test from 40 random testers chose essential oil from shade drying and microwave drying methods as the most preferred types. Overall, microwave drying seems to be the ideal method for initial processing of raw material for the Makwhean essential oil.